Initial Proportion and Dynamic of B.1.1.7 SARS-CoV-2 in a Large City in the West of Germany - Simon D. Herkenrath; Kyrill Boschung; Julia A. Nacov; Annette Heibges; Britta Schroer; Marcel Treml; Winfried J. Randerath (Biomedicine Hub, 2022)
Rationale: Several mutational variants of SARS-CoV-2 have been identified in the past months with increasing prevalence worldwide. Some variants, such as B.1.1.7, are of high relevance due to increased transmissibility, facilitating virus spread and calling for stricter containment measures. Objectives: The aim of this study was to examine proportion and dynamic of B.1.1.7 in SARS-CoV-2-positive samples in a large city in the west of Germany. Methods: Consecutive SARS-CoV-2-positive samples from a local outpatient clinic, obtained over a period of 4 weeks (mid-January to mid-February 2021), were examined for the presence of the variant B.1.1.7. The size of B.1.1.7 infection clusters was compared with non-B.1.1.7 clusters. The transmissibility of SARS-CoV-2 variant B.1.1.7 was described based on corresponding cases of an infection cluster in a local child daycare centre. Results: Among 226 SARS-CoV-2-positive cases, B.1.1.7 was detected in 74 subjects (33%). The 7-day moving mean of the B.1.1.7 proportion started at 20% and reached 50% only 3 weeks later. B.1.1.7 clusters comprised 10.7 ± 12.1 persons per cluster, while non-B.1.1.7 clusters were considerably smaller (5.1 ± 5.8). One specific B.1.1.7 infection cluster in a 40-children daycare centre started with one teacher leading to 11 infected children and 8 infections among teachers. The infection spread to 6 families and one other daycare centre, with a total 43 SARS-CoV-2-positive subjects. Conclusions: We found a rapid increase in the SARS-CoV-2 variant B.1.1.7 with larger infection clusters than non-B.1.1.7. These results suggested a rapid increase in the B.1.1.7 proportion and a renewed increase in the total number of SARS-CoV-2 infections for the time following the analysed period. Considering the rapid emergence and spread of viral variants, close monitoring of mutation events is essential. Therefore, routine whole-genome sequencing appears to be useful in addition to searching for known mutations.